Plasma microRNA signature is associated with risk stratification in prostate cancer patients. Issue 6 (23rd June 2017) - Al‐Qatati, Abeer; Akrong, Christine; Stevic, Ines; Pantel, Klaus; Awe, Julius; Saranchuk, Jeff; Drachenberg, Darrel; Mai, Sabine; Schwarzenbach, Heidi
Abstract : The aim of this study was to establish a unique expression profile of circulating cell‐free microRNAs (miRNAs) capable of differentiating between prostate cancer (PCa) patients with high‐risk and intermediate‐risk Gleason scores. MiRNA expression profiles were determined in plasma samples from 79 treatment‐naïve PCa patients, 1–2 follow‐up samples after radical prostatectomy (RP) from 51 out of the 79 PCa patients, and 33 healthy men, using a quantitative real‐time PCR‐based array containing 48 selected miRNAs. We identified 27 up‐ and 2 downregulated plasma miRNAs in PCa patients compared with healthy men. Most of the upregulated miRNA levels were also associated with increasing PSA levels and Gleason scores. Particularly, the levels of miR‐16 ( p  = 0.002), miR‐148a ( p  = 0.006) and miR‐195 ( p  = 0.006) significantly correlated with high‐risk Gleason scores, whereby miR‐148a ( p  = 0.003) was also significantly associated with increasing PSA values. The high miRNA levels before RP remained increased in the postsurgical plasma samples. Our findings show a network of deregulated plasma miRNAs. In particular, miR‐16, miR‐148a and miR‐195 are involved in the regulation of the PI3K/Akt signaling pathway. These miRNAs may be promising therapeutic targets for high‐risk PCa stratification. Abstract : What's new? Existing diagnostic tests for prostate cancer are suboptimal in specificity and sensitivity, raising the risk of overdiagnosis and overtreatment. To circumvent these issues, novel tumor‐ and stage‐specific biomarkers that can be incorporated into diagnostic testing are needed. This study describes a unique expression profile of circulating microRNAs (miRNAs) in prostate cancer patients that effectively differentiates between patients at intermediate versus high risk for recurrence or death after surgery. In particular, miR‐16, miR‐148a, and miR‐195 were strongly associated with high‐risk Gleason scores. The data suggest that specific plasma miRNAs can help identify high‐risk patients and potentially facilitate treatment decisions.